Sacred Justice: The Autonomy of Traditional Villages in Resolving Customary Disputes in Bali - Prasada, Dewa Krisna; Ni Putu Sawitri Nandari; Kadek Julia Mahadewi; Komang Satria Wibawa Putra (JUSTISI, 2025)
The aim of this study is a fundamental part of Indonesia's state structure, as it has existed since Indonesia's independence and has been recognized within the legal framework. This recognition is enshrined in Article 18B of the 1945 Constitution and reinforced by Law No. 6 of 2014 on Villages. In Bali, customary law communities, known as krama desa, have special rights, including autonomous governance over local affairs. This study focuses on the autonomy of customary villages in Bali, particularly in resolving customary disputes. The study method used is normative legal research with a legislative approach, analyzing the legal provisions governing customary villages and their dispute resolution mechanisms. The novelty of this research contributes to the discourse on legal certainty and justice for customary law communities by clarifying the extent of the authority of customary villages in resolving customary law violations. The results of the study indicate that customary villages in Bali have legal authority to resolve customary law violations, as stipulated in Article 104(d) of the Village Law and Article 24(l) of the Bali Customary Village Regulation. This affirms their role in maintaining order through customary law traditions. In conclusion traditional villages in Indonesia, including in Bali, are constitutionally recognized and granted autonomy in governance and dispute resolution. To enhance legal certainty, traditional villages should establish clear procedural guidelines (awig-awig) for resolving disputes through traditional deliberative assemblies (paruman adat). This approach can ensure justice while maintaining environmental and social harmony within the customary legal system.